2020
DOI: 10.1038/s41598-020-59921-4
|View full text |Cite
|
Sign up to set email alerts
|

Maturational delay and asymmetric information flow of brain connectivity in SHR model of ADHD revealed by topological analysis of metabolic networks

Abstract: Attention-deficit hyperactivity disorder (ADHD) is a complex brain development disorder characterized by hyperactivity/impulsivity and inattention. A major hypothesis of ADHD is a lag of maturation, which is supported mainly by anatomical studies evaluating cortical thickness. Here, we analyzed changes of topological characteristics of whole-brain metabolic connectivity in twelve SHR rats selected as ADHDmodel rats by confirming behavior abnormalities using the marble burying test, open field test, and delay d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 54 publications
(52 reference statements)
0
14
0
Order By: Relevance
“…Children/adolescents (7.2–21.8 years) with ADHD were found to have a functional maturation lag in the DMN ( Sripada et al., 2014b ), and young ADHD rats (4–6 weeks) had a lag in limbic regions ( Ha et al., 2020 ). Here, we found that the limbic system dominantly affected by ADHD can better predict hyperactivity in ADHD patients, but not in HCs.…”
Section: Discussionmentioning
confidence: 99%
“…Children/adolescents (7.2–21.8 years) with ADHD were found to have a functional maturation lag in the DMN ( Sripada et al., 2014b ), and young ADHD rats (4–6 weeks) had a lag in limbic regions ( Ha et al., 2020 ). Here, we found that the limbic system dominantly affected by ADHD can better predict hyperactivity in ADHD patients, but not in HCs.…”
Section: Discussionmentioning
confidence: 99%
“…This animal model exhibits the behavioral characteristics of the disorder ( Sagvolden, 2000 ) and displays several variations in the Dat1 gene encoding the dopamine transporter ( Mill et al, 2005 ), known to be related to ADHD ( Cook et al, 1995 ; Faraone et al, 2005 ; Madras et al, 2005 ). Finally, conventional neuroimaging studies have shown structural and functional alterations in SHR rats similar to those observed in ADHD ( Danker and Duong, 2007 ; Huang et al, 2016 ; Ha et al, 2020 ).…”
Section: Discussionmentioning
confidence: 81%
“…Given the several cortical and sub-cortical structures implicated in pursuit triggering [24], the absence of a developmental effect on pursuit performances in children with ADHD could be due to a shift of maturation processes (immaturity) of the areas involved in pursuit eye movements. A major hypothesis of ADHD suggested a lag of maturation of brain structures, which is supported mainly by anatomical studies evaluating cortical thickness [25]. These anatomical studies could explain the hypothesis on the immaturity of cortical structures responsible for pursuit triggering.…”
Section: Pursuit Performance Was Not Sensitive To a Developmental Effect In Adhdmentioning
confidence: 97%